Oral health-related quality of life and dental occlusion before and after alveolar and hard palate reconstruction at the time of mixed dentition - González-Olivares, Hilda; Jáuregui-Renaud, Kathrine (Frontiers in Oral Health, 2025)
AimIn children 8–10 years old with not syndromic cleft lip and palate (nsCLP) and intentionally unrepaired nasoalveolar fistula, to assess the difference in oral health-related quality of life before and 6 months after the reconstruction, compared to age matched children with no birth abnormalities, considering dental occlusion.Methods52 children participated in the study, 26 with nsCLP and 26 with no birth abnormalities. At inclusion in the study, dental occlusion was assessed by the Angle classification and the Dental Aesthetic Index in all the participants, and also by the GOSLON yardstick index in participants with nsCLP. Oral health-related quality of life was evaluated by the Child Perceptions Questionnaire (CPQ8-10) twice, with 6 months in between. Bivariate and repeated measures multivariate analyses were performed with p ≤ 0.05.ResultsIn participants with/ without nsCLP, oral-health related quality of life was significantly related to dental occlusion and to age. In participants with nsCLP, after reconstruction, quality of life improved mainly on the emotional and social well-being domains, with influence and interaction between age and dental occlusion.CommentIn children with nsCLP and intentionally unrepaired nasoalveolar fistula, the earliest possible repair could be beneficial for their emotional and social well-being. To start prompt orthopaedic treatment, early evaluation of dental occlusion should be promoted in both children with and without nsCLP.